PENGARUH PERTUMBUHAN EKONOMI, TINGKAT PENGANGGURAN TERBUKA, DAN PERSENTASE BUTA HURUF TERHADAP KEMISKINAN DI INDONESIA - B61108022, MARIA NORTINAYATI (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT Influence Economic Growth, Open Unemployment Rate, and Percentage of Illiterate to Poverty in Indonesia This study with respect to the economic growth, open unemployment rate, and percentage of illiterate to poverty in Indonesia. The method used to determine the effect of these is the method of associative or causal design. Associative or causal design method is useful for analying research relationships betwen one variable with another variable or how one variable affects the other variabel. The Population in this research is all the province of Indonesia consisting of 33 province. The samples are part of the population, from this statment that the samples taken in this study at 100%, so the sample size is a total 33 province in Indonesia. This reserch uses panel data which combines time series data (for 5 years, that is 2007 to 2011) and the cross section data for province in 33, thus forming the observed amount of data as much as 48 data (33 province over a period of 5 years). In this reserch, quantitative analysing is used in order to test and analyze whether there is an influence of economic growth, open unemployment rate, and percentage of illiterate to poverty in Indonesia using Multiple Linear Regression analysis tool. The result is a economic growth variable significantly and negative to the poverty, open unemployment rate variable significantly and positive to the poverty, percentage of illiterate variable significantly and positive to the poverty. Keywords : economic growth, open unemployment rate, percentage of illiterate, poverty